The Pengaruh Rasio Keuangan, Likuiditas Dan Firm Size Terhadap Profitabilitas Pada Perusahaan Sektor Konsumen Primer Sub Sektor Sawit (CPO) Yang Terdaftar Di Bursa Efek Indonesia 2017-2021: Study on Consumer Non-Cyclical Sector Companies of Palm Sub Sector (CPO) Listed on The Indonesia Stock Exchange 2017-2021 - Lidya Sarai; Muhammad Nuryatno Amin (Politeknik Ganesha Medan, 2023)
This study aims to analyze the ratios of finance, liquidity, and company size to profitability which are used as the dependent variable in this study. The data in this study were obtained from the financial reports of palm oil companies (CPO) listed on the Indonesia Stock Exchange (IDX) for 2017-2021. The sample for this study consisted of 13 companies selected using a technique known as purposive sampling. Using multiple linear regression analysis, the relationship between the variables investigated in this study. The analytical tool used is SPSS veirsion 25.0. The results of this study, partially Working Capital to Total Assets, Inventory Turnover, Liquidity and Firm Size have a positive effect on Profitability, while the Debt to Equity Ratio has a negative effect and Total Asset Turnover does not have a significant effect on Profitability in primary consumer sector companies in the oil palm sub-sector (CPO) listed on the IDX 2017-2021. Simultaneously, all variables have a positive and significant effect on profitability.